Fontes nitrogenadas associadas a diferentes formas de apresentação do grão de milho para bovinos confinados - Porsch, Renata Volpatto (2017)
This experiment aimed to evaluate the replacement of soybean meal by non-protein nitrogen sources (NPN) in combination with ground or whole corn in the diet concentrate fraction of confined cattle on the dietary intake, blood protein metabolite analyzes, and performance and ingestive behavior. The experiment was developed at the Laboratório de Bovinocultura de Corte of the Department of Zootechnics of UFSM. We used 53 steers, with Charolais or Nellore predominance, with initial mean age and weight of 22 months and 250 kg. Experimental diets contained voluminous:concentrate ratio of 50:50 based on dry matter. The treatments were: soybean meal + whole grain corn; soybean meal + milled corn; common urea + whole grain corn; common urea + milled corn; protected urea + whole grain corn; protected urea + milled corn. The experimental design was completely randomized in a 3x2 factorial scheme. There was no significant interaction between nitrogen source and corn grain form for any of the variables studied (P>0.05). Dry matter and crude protein intakes were higher for animals fed with soybean meal both in kg and in kg/100 live weight. Daily weight gain was higher for steers fed with soybean meal (1,600 kg/day) vs common urea (1,238 kg/day) and protected urea (1.217 kg/day). Corn presentation did not reflect any differences in the parameters of consumption, performance and behavior. The concentration of circulating albumin showed a significant interaction between nitrogen source and date of collection (P<0.05). Animals fed with soybean meal presented increasing albumin over the experimental period, while animals fed with NPN had growth in albumin levels from the first to the second collection, stabilizing up to the end of the study. The values of globulin presented interaction of the dates of collection with nitrogen sources and also with forms of corn grain, having an inverse behavior to the value of albumin. The albumin/total protein ratio increased throughout the experimental period, except for steers that consumed protected urea, which had similar values between the first and last collection. Feeding time of soybean meal was higher than protected urea, while common urea had intermediate behavior. Idling time differed among all treatments, with superiority to soybean meal, while common urea was higher than protected urea. NPN sources promoted higher rumination time and number of chewing per ruminal bolus and lower ruminating efficiencies of DM and NDF than soybean meal (P<0.05). Higher daily chewing times were observed for protected urea, followed by common urea, which was higher than soybean meal. In the number of chews similar behavior was observed, only with common urea presenting intermediate values. The use of true protein source in the diet of confined steers provides better results in aspects of performance, blood metabolites and ingestive behavior in relation to NPN in the two evaluated forms.